SERS and DFT studies of 2‐(trichloroacetyl)pyrrole chemisorbed on the surface of silver and gold coated thin films: In perspective of biosensor applications. Issue 11 (7th July 2021) - Premkumar, R.; Hussain, Shamima; Koyambo‐Konzapa, Stève‐Jonathan; Jayram, Naidu Dhanpal; Meera, M.R.; Mathavan, T.; Benial, A. Milton Franklin
Abstract: The adsorption and orientations of 2‐(trichloroacetyl)pyrrole (TCAP) adsorbed on a fabricated silver‐coated thin film (SCF), and gold‐coated thin film (GCF) were investigated using surface‐enhanced Raman scattering (SERS) studies and compared with the normal Raman scattering (nRs) spectrum of TCAP. The observed nRs and SERS spectra of TCAP were validated theoretically using DFT quantum chemical calculations. Initially, the molecular structure of TCAP, TCAP‐Ag3, and TCAP‐Au4 molecular systems were optimized and analyzed. The fabricated SCF and GCF are characterized using FESEM analysis, which confirms that the silver and gold nanoparticles of the corresponding films are spherical in shape. The obtained significant red‐shift in UV‐visible spectra of TCAP added on SCF and GCF surfaces reveal that the TCAP strongly adsorbed on SCF and GCF surfaces. The frontier molecular orbitals analysis authenticates the charge‐transfer interaction from Ag3 and Au4 metal clusters to the TCAP molecule, leading to the adsorption of TCAP molecule on Ag3 and Au4 metal clusters, which validates the UV‐vis results. SERS spectral analysis confirms that the TCAP chemisorbed on SCF and GCF surfaces with tilted orientation and the corresponding results were validated theoretically. The calculated SERS enhancement factor values illustrate that the GCF surface exhibits a higher SERS signal enhancement than the SCF surface. Therefore, the present investigation will be useful for the development of active SERS substrates and pyrrole‐related biosensors.